Children's toothache is becoming everybody's business: where do parents go when their children have oral pain in London, England? A cross-sectional analysis. Issue 2 (28th February 2018) - Muirhead, Vanessa Elaine; Quayyum, Zahidul; Markey, Donal; Weston-Price, Sally; Kimber, Annette; Rouse, Wayne; Pine, Cynthia M
Abstract : Objectives: To assess the number of parents who visited community pharmacies in London seeking pain medications for their children's pain and specifically for oral pain, to identify which health services parents contacted before their pharmacy visit and to estimate the cost to the National Health Service (NHS) when children with oral pain who visit pharmacies also see health professionals outside dentistry. Design: A cross-sectional study. Setting: 1862 pharmacies in London in November 2016–January 2017. Participants: Parents, carers and adolescents purchasing over-the-counter pain medications or collecting pain prescriptions for children (0–19 years). Brief intervention: A survey administered by pharmacy staff to participants and a guidance pack. Main outcome measures: The number of parents who visited pharmacies seeking pain medications for their children's pain and oral pain and the number of parents who contacted health professionals outside dentistry before their pharmacy visit. Estimated costs of visits by children with oral pain to health professionals outside dentistry. Results: One in two (951) pharmacies participated collecting information from 6915 parents seeking pain medications for their children. The majority (65%) of parents sought pain medications to relieve their children's oral pain. Only 30% of children with oral pain had seen a dentist before the pharmacy visit, while 28% of children had seen between one and four different health professionals. The cost to the NHS of children contacting health professionals outside dentistry was £36 573, extrapolated to an annual cost of £373 288. Replicating these findings across all pharmacies in England could mean that the NHS spends an estimated £2.3 million annually when children with oral pain inappropriately use multiple health services. Conclusion: Most parents who visited pharmacies for children's pain medications in London sought pain medications for children's oral pain. Children's inappropriate contact with multiple health services when they have oral pain adds significant costs to the NHS.